Appraisal Theory: Can It Be Applied to Visual Images in Isolation to the Text? - Bashayir AlZahrani; Mohammed Alhuthali (European Scientific Journal, ESJ, 2024)
The role of women in Saudi society is evolving; however, the process of reform is subject to multiple interpretations. This makes the role of resemiosis when interpreting visual media particularly important, perhaps more than a direct focus on the semiotic modes adopted. Data was collected from a variety of on-line media covering the recent changes. Appraisal Theory was used to capture the judgement process in terms of emotions experienced by the reader/viewer and how the wider context such as the full news article, or even just the headline, forms a part of this process.  This posits that in contested situations, resemiosis is a critical part of the process and sometimes the apparent interpretation of a single image (intersemiosis) can be different to the interpretation of the whole. In such instances, different semiotic modes convey different meanings but a focus on one in isolation can be misleading as to the overall intent.